The Crypto Shelter: A Safe Haven for Equity Market during the COVID-19 Pandemic - Pornpikul, Chanapol (Journal of Business, Innovation and Sustainability (JBIS), 2023)
This study analyzes cryptocurrencies as a safe haven from the equity market during the Covid-19 pandemic from April 2020 to December 2021 and compares these with two traditional safe-haven assets, gold and US government bonds, by using the multiple linear regression model. This study hypothesizes that Bitcoin or “digital gold” can be a safe haven and a store of value during financial turbulence. However, our empirical results show that Tether performs a better safe-haven function than Bitcoin, other cryptocurrencies, and the two traditional shelters, gold and US government bonds. Tether also exhibits low volatility and negatively correlates with equity sample portfolios. However, it could not serve as a shelter during all the periods considered. Thus, investors can benefit from Tether to store the value of their portfolios during times of high market volatility. They should also consider their investment portfolios to find shelter and rebalance them for turbulent times. The limitation of this study does not investigate other properties of Bitcoin and cryptocurrencies, such as a medium of exchange as money, and it can be explored for further research.